Impact of economic growth on carbon emissions in selected West African countries, 1980–2019 - Richard Osadume; Edih O. University (Journal of Money and Business, 2021)
Purpose – This study investigated the impact of economic growth on carbon emissions on selected West African countries between 1980 and 2019. Simon-Steinmann's economic growth model provides the relevant theoretical foundation. The main objective of this study was to ascertain whether economic growth will impact carbon emissions. Design/methodology/approach – The study selected six-sample countries in West Africa and used secondary data obtained through the World Bank Group online database covering the period 1980–2019, employing panel econometric methods of statistical analysis. Findings – The outcome indicates that the independent variable showed a positively significant impact on the dependent variable for the pooled samples in the short-run, with significant cointegration. Research limitations/implications – The study concluded that economic growth significantly impacts the emissions of carbon, and a 1% rise in economic growth will result to 3.11121% unit rise in carbon emissions. Practical implications – Policy implementation should encourage the use of energy efficient facilities by firms and government and the establishment of carbon trading hubs. Social implications – Failure by governments to heed the recommendations of this research will result to serious climate change issues on economic activities with attendant consequences on human health within the region and globally. Originality/value – This is one of the comprehensive works on subject covering the West African region within the continent.